2012
DOI: 10.1180/claymin.2012.047.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aluminium incorporation in the preparation of zirconia-pillared clay and catalytic performance in the acetalization reaction

Abstract: The exchange reaction of Na-bentonite with zirconium pillars gives products which suffer from a loss of crystallinity, with basal spacing about 18 Å and surface area of 200 m2 g–1. Aluminium introduced in different amounts in the zirconium intercalated solution leads to an improvement in the stability and crystallinity of zirconia-pillared clays (Zr-PILCs) and creates pillared clays with new properties. Adding a small amount of Al (10 molar %) leads to an increase of d001 from 18 Å to 20.5 Å and an increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This bentonite has been thoroughly characterized in previous works [11][12][13][14]. The impurities are mainly quartz and calcite.…”
Section: Methodsmentioning
confidence: 99%
“…This bentonite has been thoroughly characterized in previous works [11][12][13][14]. The impurities are mainly quartz and calcite.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in the literature related to zirconia-pillared clay and the combination of zirconia with aluminum-pillared montmorillonite are limited, although ZrO 2 is a well-known active metal oxide catalyst utilized in many chemical reactions. Previous investigations have revealed that ZrO 2 pillarization significantly affected the montmorillonite’s catalytic activity in some organic reactions, including the linear alkylation of benzene, acylation of diol, and acetylation, while ZrO 2 dispersed into aluminum-pillared saponite has been used for NOx selective catalytic reduction (SCR) and phenol hydroxylation [13–16] . Al-pillared montmorillonite enhances the catalytic activity of ZrO 2 , while the ZrO 2 increases the catalyst stability.…”
Section: Introductionmentioning
confidence: 99%